Psikologi dalam pengucapan awam yang dinamik dan berkesan - 403780 Mohd. Sofian Muhamad Yusof; Rosli Jamil Ahmad Zainuddin; Mariani Mohd. Nor (Kuala Lumpur : Utusan Publications & Distributors Sdn Bhd ., 2007)
34